2011
DOI: 10.1111/j.1752-1688.2011.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital Hydrologic Networks Supporting Applications Related to Spatially Referenced Regression Modeling1

Abstract: Digital hydrologic networks depicting surface-water pathways and their associated drainage catchments provide a key component to hydrologic analysis and modeling. Collectively, they form common spatial units that can be used to frame the descriptions of aquatic and watershed processes. In addition, they provide the ability to simulate and route the movement of water and associated constituents throughout the landscape. Digital hydrologic networks have evolved from derivatives of mapping products to detailed, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 46 publications
(98 reference statements)
0
89
0
Order By: Relevance
“…Another observational product, the USGS WaterWatch runoff (Brakebill et al, 2011), was found to be more useful in this study. Derived from the comprehensive NWIS gauge observation, WaterWatch runoff is the assimilated time series of flow per unit of area calculated for each conterminous HUC8 subbasin.…”
Section: Observed Streamflow and Runoffmentioning
confidence: 98%
“…Another observational product, the USGS WaterWatch runoff (Brakebill et al, 2011), was found to be more useful in this study. Derived from the comprehensive NWIS gauge observation, WaterWatch runoff is the assimilated time series of flow per unit of area calculated for each conterminous HUC8 subbasin.…”
Section: Observed Streamflow and Runoffmentioning
confidence: 98%
“…Therefore, the USGS WaterWatch runoff [5] was used to provide observational runoff measurements. WaterWatch runoff is the assimilated monthly time series of flows per unit of area calculated for each conterminous 8-digit hydrologic unit (HUC8), derived from the comprehensive gauge observation network (thousands of gauges nationwide) that is maintained by the USGS NWIS (national water information system).…”
Section: Data Sourcesmentioning
confidence: 99%
“…The load generated within upstream reaches and transported to the reach through the stream network. Digital hydrologic network The MRB_E2RF1 digital hydrologic network and associated attribute data were developed by Brakebill and Terziotti (2011).…”
Section: Strategymentioning
confidence: 99%